2015
DOI: 10.1007/s00125-015-3618-4
|View full text |Cite
|
Sign up to set email alerts
|

GIP increases adipose tissue expression and blood levels of MCP-1 in humans and links high energy diets to inflammation: a randomised trial

Abstract: Aims/hypothesis Obesity is associated with elevated monocyte chemoattractant protein-1 (MCP-1), a proinflammatory chemokine related to diabetes and cardiovascular disease. Since obesity is triggered by energy dense diets, we hypothesised that nutrient induced intestinal hormones such as glucose-dependent insulinotropic peptide (GIP) may directly stimulate the release of chemokines from adipose tissue and induce low-grade inflammation. Methods GIP effects on gene expression and secretion of inflammatory markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 42 publications
5
50
0
4
Order By: Relevance
“…5d) Although we have employed a highly complex protocol with 13 colour FACS sorting of adipose SVF to characterise WAT residing cell populations, the study has some methodological limitations, among which the amount of patient material and small cohort size are most important. Although the number of participants included in the study (n=27) matches well a number reported in many other studies where in-depth characterisation of adipose tissue has been performed [44][45][46], the current dataset should be considered as a pilot report and further studies in larger independent cohorts need to be performed to further strengthen key results. Furthermore, samples obtained by needle biopsies were too small (2.33±1.05 g) and obtained yields of SVF cells (243,500±142,325 cells) were not sufficient to enable analyses of immune cell activation or cytokine secretion as well as differentiation of sorted progenitor cells.…”
Section: Discussionsupporting
confidence: 58%
“…5d) Although we have employed a highly complex protocol with 13 colour FACS sorting of adipose SVF to characterise WAT residing cell populations, the study has some methodological limitations, among which the amount of patient material and small cohort size are most important. Although the number of participants included in the study (n=27) matches well a number reported in many other studies where in-depth characterisation of adipose tissue has been performed [44][45][46], the current dataset should be considered as a pilot report and further studies in larger independent cohorts need to be performed to further strengthen key results. Furthermore, samples obtained by needle biopsies were too small (2.33±1.05 g) and obtained yields of SVF cells (243,500±142,325 cells) were not sufficient to enable analyses of immune cell activation or cytokine secretion as well as differentiation of sorted progenitor cells.…”
Section: Discussionsupporting
confidence: 58%
“…Доказано, что снижение «инкретинового эффекта» является ранней характеристикой СД2 [6]. Ис-следованиями многих авторов выявлена значительная лиганднезависимая или базальная активность рецептора GIPR, что может играть важную роль в регуляции уровня глюкозы в крови [13][14][15][16]. Предполагают, что о функци-ональной роли GIPR можно судить не только по пост-прандиальной секреции гормонов поджелудочной железы (инсулина и С-пептида), а также и по их уров-ням натощак, что косвенно может отражать базальную активность GIPR [13,14,15].…”
Section: результаты и обсужденияunclassified
“…Ис-следованиями многих авторов выявлена значительная лиганднезависимая или базальная активность рецептора GIPR, что может играть важную роль в регуляции уровня глюкозы в крови [13][14][15][16]. Предполагают, что о функци-ональной роли GIPR можно судить не только по пост-прандиальной секреции гормонов поджелудочной железы (инсулина и С-пептида), а также и по их уров-ням натощак, что косвенно может отражать базальную активность GIPR [13,14,15]. Физиологическое значение такой конститутивной активности рецептора не совсем понятно, однако известно, что полиморфные варианты GIPR могут способствовать изменению его базальной активности [17].…”
Section: результаты и обсужденияunclassified
“…However, rats fed a HF diet demonstrated increased plasma levels of MCP-1 by more than 10% compared to rats on the C diet (Figure 5), and the rats fed the HFS diet (supplemented with N -caffeoyltryptamine (2 mg per day)) demonstrated significantly lower plasma MCP-1 levels than those fed the HF diet ( p < 0.05), and even slightly lower than those on the control diet (Figure 5). Because plasma levels of MCP-1 are commonly used as a risk indicator for CVD including atherosclerosis [11,12], and because a high-calorie diet often increases plasma levels of the MCP-1 protein in humans [24], these data suggest that N -caffeoyltryptamine may have positive effects in lowering the plasma levels of MCP-1 in individuals with cardiovascular risks fed a high-calorie diet.…”
Section: Resultsmentioning
confidence: 99%